CLINICAL AND LABORATORY DIAGNOSTICS OF ACUTE BRONCHITIS - Turakulov Javlon Sodik ugli; Ibragimova Nadiya Sabirovna; Tursunov Feruz Uktamovich; Abdullaeva Dilshoda Alijon kizi (Web of Journals Publishing, 2025)
The relevance of the topic of acute bronchitis is due to its high prevalence and significant impact on the quality of life of patients. Acute bronchitis, an inflammation of the bronchial tree, often occurs after viral infections, which makes it especially relevant during cold and flu season. In recent years, there has been an increase in the number of cases of the disease in both children and adults, which requires a careful approach to diagnosis and treatment. In addition, improper treatment or ignoring the disease can lead to chronicity of the process and the development of more serious diseases, such as chronic obstructive pulmonary disease. Studying acute bronchitis is also important from a public health perspective, as it may contribute to overall morbidity and demand for medical resources.
Keywords: Acute bronchitis, laboratory diagnostics, microbiological examination, spirometry, pulse oximetry, prognosis.